Ethics and journalistic challenges in the age of artificial intelligence: talking with professionals and experts - Gutiérrez-Caneda, Beatriz; Lindén, Carl-Gustav; Vázquez-Herrero, Jorge (Frontiers in Communication, 2024)
The rapid advancement of artificial intelligence (AI) is transforming the media industry by automating processes, with applications in data analysis, automated writing, format transformation, content personalization, and fact-checking. While AI integration offers new opportunities in journalism, it also raises ethical concerns around data privacy, algorithmic biases, transparency, and potential job displacement. This study employed qualitative interviews with media professionals and researchers to explore their perspectives on the ethical implications of AI integration in newsrooms. Interview data were analyzed to identify common themes and specific challenges related to AI use in journalism. The findings discuss issues such as the tensions between technology and journalism, ethical challenges related to AI, the evolution of professional roles in journalism, media guidelines, and potential future regulations.